??THE DEFECT STRUCTURE OF (Fel - XCO)2 RE COMPOUNDS (RE = Gd AND Tb) - ATIQ, S.; RAWUNGS, R.D.; WEST, D.R.F; QAZI, ANDM.A. (Biological Sciences - PJSIR, 1994)
Constitutional investigations of Fe-RE, Co-RE and Fe-Co-RE systems revealed that it requires an "RE" content in excess of (Fe] - x Cox)z RE composition in orderto prepare these compounds free from the presence of phases. A comparison of experimental and theoretical densi ties (calculated from the volumes of the unit cells) showed that the number ofvacantTM (TM=Fe, Co or Fc–Co) sites vary from 7.5% for (Feo.32COo.6s)Pd to 2.5% in the binary Fe.Gd compound. Likewise, there are 7.1 % such sites in (FeO.33 COO.67)Z Tb and 3.8% in the binary Coz Tb compound. Thus, it was concluded that the defects in the lattices of these compounds, responsible for the deviation from ideal stoichiometric compositions are vacancies on Fe and Co sites in respective binary compounds and on Fe+Co sites in ternary compounds.